TRANSFORMATIONS - Ďuroška, Tomáš (Ecotech Systems s.r.o., 2023)
Poems which break it all down into atoms. They deal with fundamental topics. They ask questions and look for answers. They hold up a mirror to us as well as motivating us to make improvements.